Fifteenth General Review of Quotas : Additional Considerations and Data Update. (Policy Papers; Policy Paper, 2021)
This paper provides background for a further round of discussions on the Fifteenth General Review of Quotas (hereafter 15th Review). The paper builds on work presented in previous staff papers and Directors' views expressed in three meetings of the Committee of the Whole in September 2017 and February 2018. No proposals are presented at this stage, pending further Board guidance on possible approaches to narrowing the current differences of views.